Particulate Monitoring Around Frac Sand Plants Using EPA-Certified Monitors - Ruijian, Liang; Wetzel, Ian; Schmitz, Jennifer; Aragon, Sara; Awad, John; Yang, Johnny; Lor, Seleta; Fuhrman, Ethan (My University, 2015)
The purpose of this study was to investigate the environmental and health impacts caused by hydraulic sand fracking. The data collected by EPA-certified instruments will continue to reflect concerns with elevated PM2.5 levels from our previous measurements.
Color poster with text, charts, graphs, maps, and photographs.
Keywords: Frac sand; Sand mining; Hydraulic fracturing; Posters